(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aimed to identify The level of teachers’ practice of psychological and social climate management skills, and the level of classroom discipline problems from the perspective of teachers themselves. And to know the relationship between them. The descriptive approach was used to verify the validity of the research hypotheses. The study sample consisted of (89) teachers of the basic education/ first stage in Tartous city for the year 2016/2017, based on a questionnaire constructed by the researcher for this purpose. Which consists of two areas (management of psychological and social climate - classroom discipline problems) after verifying the validity and reliability, and a statistical program for educational and psychological (spss) was used. The research reached the following results: The mean value of the psychological and social climate management field was (4.2165) with a standard deviation (27456). It is a high value within a scale that "always". The degree of prevalence of class discipline problems was law. The average value was (1.9363) with a standard deviation (47,493), There is a strong inverse relationship between practicing psychosocial and social climate management skills and class discipline problems. The researcher concludes a number of suggestions like: preparing and training students teachers on the positive classroom discipline skills, to prevent behavioral problems and raise their level of managing the psychological and social climate in the classroom, conducting more studies about the subject.